Foraging strategies of grey-headed albatrosses Thalassarche chrysostoma: Integration of movements, activity and feeding events - Catry, Paulo (2012)
We identified a range of foraging strategies adopted by grey-headed albatrosses Thalassarche chrysostoma rearing chicks at Bird Island, South Georgia, by simultaneously using satellite telemetry, wet/dry activity recorders and stomach temperature loggers. The albatrosses foraged mostly over oceanic waters, probably associated with the Polar Front north of South Georgia, and also over shelf-slope waters around the Antarctic Peninsula. After leaving the colony, birds commuted to areas with predictable prey concentrations, where they remained for several days. During search periods, birds landed more often and had a higher intake rate, but spent the same proportion of time in flight as on commuting days. Although intake rates were particularly high in shelf-break waters around the Antarctic Peninsula (only one individual foraged in this area), prey were also consumed in reasonable quantities during commuting flights. While at sea, birds spent most (81%) of the day flying, and most (94%) of the night resting on the water. A considerable proportion (26% by mass) of prey was consumed during darkness. The majority of prey were detected and captured during search flights, but 35% were located while sitting on the sea surface. Many ingestion events (up to 27% of the overall food intake) showed temperature signatures characteristic of fluids, suggesting that albatrosses may feed on gelatinous and rapidly digested prey (e.g. salps and jellyfish) much more often than previously suspected. Diet samples delivered to the chicks comprised mostly squid (particularly Martialia hyadesi) and Antarctic krill Euphausia superba.